2019
DOI: 10.1021/acs.jpcc.9b03165
|View full text |Cite
|
Sign up to set email alerts
|

Cooperative Action of Laser-Induced Thermal Effects and Ionic Coordination on the Order of TPPA0 Porphyrin Derivatives Self-Assembled Interface Probed via Real-Time Second Harmonic Generation

Abstract: We performed real-time second harmonic generation (SHG) to study the cooperative action of laser-induced thermal effects and ionic coordination on the order/disorder of TPPA0 (5,10,15,20-(tetrakis((ethoxycarbonyl)methoxy)phenyl)porphyrin) monolayers on the interface of three aqueous solutions. Time dependence curves of SH signals of TPPA0 monolayers on pure water and ZnCl 2 aqueous and CuCl 2 aqueous interfaces were detected under the polarization combinations of p-in/p-out, s-in/p-out and 45°-in/s-out. All th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

4
1

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 42 publications
1
6
0
Order By: Relevance
“…Subsequently, the broadening of the molecular orientation distribution of D289 was taken into account to understand the decrease in the SHG signal. Previous studies have reported that a broader distribution has to be used when the orientation angle and number density cannot explain the intensity variation under the assumption of δ distribution of adsorbed molecules at the interface. Here, we performed a simulation to investigate the effect of the width of the orientation distribution on the orientation functional R ( θ ), as shown in Figure c. Figure d illustrates the relationship between the orientation functional R ( θ ) and the full width at half-maximum (fwhm) when the orientation angle was set at 30°.…”
Section: Resultsmentioning
confidence: 99%
“…Subsequently, the broadening of the molecular orientation distribution of D289 was taken into account to understand the decrease in the SHG signal. Previous studies have reported that a broader distribution has to be used when the orientation angle and number density cannot explain the intensity variation under the assumption of δ distribution of adsorbed molecules at the interface. Here, we performed a simulation to investigate the effect of the width of the orientation distribution on the orientation functional R ( θ ), as shown in Figure c. Figure d illustrates the relationship between the orientation functional R ( θ ) and the full width at half-maximum (fwhm) when the orientation angle was set at 30°.…”
Section: Resultsmentioning
confidence: 99%
“…The interfacial chirality was characterized using a customized nonlinear SHG-LD setup based on a typically reflected geometry, as shown in Figure . A broadband tunable mode-locked femtosecond (fs) Ti:sapphire laser (Tsunami 3960C, Spectra-Physics) was used with a pulse width of 80 fs and repetition rate of 82 MHz. The fundamental beam at a central wavelength of 800 nm was passed through a polarizer and a half-wave plate and then focused on the air/sample interface through an optical lens (with a focal length of 100 mm).…”
Section: Methodsmentioning
confidence: 99%
“…The interfacial chirality of the monolayers was characterized using a customized nonlinear SHG-LD setup based on a typically reflected geometry. 25 The SHG-LD setup is briefly described as follows. A broadband tunable mode-locked femtosecond Ti:sapphire laser (Tsunami 3960C, Spectra-Physics) with a pulse width of 80 fs and a repetition rate of 82 MHz was used to produce the fundamental beam at a central wavelength of 800 nm.…”
Section: ■ Experimental Sectionmentioning
confidence: 99%
“…The interfacial chirality of the monolayers was characterized using a customized nonlinear SHG-LD setup based on a typically reflected geometry . The SHG-LD setup is briefly described as follows.…”
Section: Experimental Sectionmentioning
confidence: 99%
See 1 more Smart Citation